Pengaruh Pengalaman Kerja dan Tanggungan Keluarga terhadap Produktivitas Pemanen di PTPN IV Regional II Afdeling III Kebun Dolok Ilir - Arif Sholahuddin Dalimunthe; Adi Widjajanto (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This study was conducted given the importance of harvester labor productivity as a factor supporting the achievement of palm oil production targets at PTPN IV Regional II, Dolok Ilir Estate. Labor productivity is influenced by various aspects, including work experience and the number of family dependents. A quantitative research approach was employed using simple random sampling with 30 respondents. Data were collected through questionnaires, observations, and interviews, and subsequently analyzed using validity and reliability tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²). The results indicate that the research instruments were valid and reliable. Individually, work experience had a positive but insignificant effect on harvester productivity (significance value of 0.461), whereas the number of family dependents had a positive and significant effect (significance value of 0.008). Simultaneously, work experience and the number of family dependents significantly influenced harvester productivity (significance value of 0.013). The coefficient of determination (R²) of 0.277 indicates that 27.7% of the variation in productivity can be explained by these two variables, while the remainder is influenced by factors outside the scope of this study.